PREDIKSI PENYAKIT TUBERCULOSIS (TBC) MENGGUNAKAN ALGORITMA C4.5 - Deny Febriyanto; Yogiek Indra Kurniawan (Jurnal Ilmiah SINUS, 2018)
Tuberculosis (TB) is an infectious disease caused by mycobacteria, especially Mycobacterium tuberculosis. TB disease remains one of the threats, especially in a country with low and middle economic levels. According to the World Health Organization (WHO) TB disease became one of the biggest causes of death in the world. Indonesia ranks second with the largest number of TB cases in the world. In addition, there are some symptoms and factors that can cause a person affected by TB disease. For the treatment of TB disease can be done intensively, but it takes a long time. Research in the diagnosis of disease with classification techniques using C4.5 algorithm has been done by several previous researchers and get good results. Therefore, in this research will be predicted TB disease using C4.5 algorithm. The C4.5 algorithm is chosen because it is very easy to interpret, fast, and has high precision accuracy. The results of this study is an application that can help people to make the diagnosis of TB disease from an early age.